2018
DOI: 10.1111/jocn.14544
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurses’ knowledge acquisition of diabetes care and its management: A qualitative study

Abstract: A range of suggestions are proposed to support the development of nursing education and practice in diabetes, including organisational and individual-level strategies to offer and enable access to education programmes to maintain up-to-date knowledge and skills in diabetes and effective communication for optimal diabetes self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The majority of nurses believed that the organization played an important role in improving nurses' knowledge of diabetes care by organizing workshops and seminars. Managers' support for nurses to participate in continuing diabetes education and training was perceived as a priority [35]. Past studies have shown that educational programs are effective in helping nurses bridge gaps between their knowledge and skills [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of nurses believed that the organization played an important role in improving nurses' knowledge of diabetes care by organizing workshops and seminars. Managers' support for nurses to participate in continuing diabetes education and training was perceived as a priority [35]. Past studies have shown that educational programs are effective in helping nurses bridge gaps between their knowledge and skills [22].…”
Section: Discussionmentioning
confidence: 99%
“…The second part has nine survey questions to assess nurses' perceived knowledgeability and role about provision of diabetes nutrition education [32]. In the third part, seven survey questions were included to assess the extent to which nurses' organizations had supported them in their efforts to enhance their knowledge about diabetes nutrition [35]. As well, background questions, such as age, gender, and years of experience were asked.…”
Section: Measurementmentioning
confidence: 99%
“…Nurses’ “lack of knowledge” of diabetes care has been well documented in the literature in previous studies, and our findings add to the evidence. Furthermore, numerous studies have been conducted to identify what factors influence nurses' knowledge acquisition for diabetes care (Alotaibi et al, 2018; Eaton‐Spiva & Day, 2011; Hollis et al., 2014). Despite the plethora of repeated evidence of the nurses' lack of knowledge and the risk for patients’ outcome, nothing was found in the literature about initiatives or developments announced by professional bodies regarding how to tackle this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses play an essential role in educating patients with diabetes on emotion management (Alotaibi et al, 2018). Before nurses could develop any specific interventions to relieve diabetes distress, it is critical to explore factors associating with diabetes distress among this population.…”
Section: Introductionmentioning
confidence: 99%